The Paradox of Jakarta’s Carbon Tax Policy: A Legal-Administrative Analysis of Non-Implementable Policy and International Compliance - Mulyono, Fadhel Koto Bida (CV. Social Politic Genius (SIGn), 2025)
DKI Jakarta’s climate mitigation efforts require reformulating the Motor Vehicle Fuel Tax (MVF Tax) from a “selling value” basis to an “emission” basis. However, this initiative is hindered by an acute policy paradox. The Decree of the Governor of DKI Jakarta Number 542 of 2025 grants incentives (tax discounts), which are philosophically and juridically misaligned with the disincentive mandate of Law Number 32 of 2009. This juridical-normative legal research analyzes this fundamental discrepancy using statute and conceptual approaches. The data analysis technique is operationalized through norm conflict analysis, compliance analysis, and juridical-conceptual analysis (risk mitigation). This research yields several findings. First, the de jure authority for reformulation (changing the MVF Tax basis) is normatively available by prioritizing the mandate of Law Number 32 of 2009. However, second, this policy is de facto non-implementable as long as the contradictory Decree of the Governor of DKI Jakarta Number 542 of 2025 remains in effect. Third, compliance with Article 6 of the Paris Agreement is conditional, demanding the absolute integration of regional mitigation actions into the SRN-PPI to avoid double counting. Fourth, implementation risk mitigation (regressive impact and fiscal leakage (fuel leakage)) juridically demands an imperative revenue allocation (revenue recycling) or earmarking design and inter-regional fiscal coordination. In conclusion, the MVF Tax reformulation is not merely a technical change. This policy constitutes a prerequisite requiring the revocation of paradoxical internal policies, the integration of accountability into SRN-PPI, and an equitable earmarking design. These steps are necessary to ensure legal certainty and effective climate mitigation.